Studi Transformasi Gelombang di daerah Pantai Malalayang - Raymond Jacson Georgen; Isria Miharti Maherni Putri; Muhamad Lukman Subangi; Herol Herol; Retno Fitri Astuti (DPPM Universitas Pelita Bangsa, 2022)
Malalayang coast has become one of the favorite tourist destinations in the province of north sulawesi. According to the observation, malayang coast has undergone physical changes (damage) in the coast area. Therefore, it is necessary to study the waves characteristics in malalayang coast by using physical modeling, in order to discover the dynamics process that causes erosion or changes in the coastline. However, physical modeling is very expensive and requires a large area of space. To answer these problems, one method that can be used to calculate and to visualize the wave characteristics close to real conditions is to use SMS software, especially by using the CGWAVE module. This study aimed to attain information about the wave transformation process that occurs in the coast of malalayang, so that the results can be used to develop and to secure the coast area. The research methods used in this study were using the CGWAVE module software and also using the manual method (analytically and graphically) as a validation technique. The results of this research indicates that the simulation wave propagation with north direction as the dominant direction, at a significant wave height H=0.26m and the period T=3.2s, produces waves with a height between 0.016m to 1.46m. Afterward, the results of waves direction visualization in all segments has produce the same pattern, that is north direction, especially in the deep sea area. However, the waves direction changed (turns) when the depth changes or passes obstacles, specifically when the waves pass through shallow waters. Keywords: Wave, Refraction, Diffraction, CGWAVE, Malalayang Coast